Ответы и объяснения

2013-05-19T13:08:51+00:00

у=2-3х;                      у+3х = 2  (все члены умножить на -4);         -4у - 12х = -8;

5х+4у= -6;                5х+4у = -6;                                                             4у + 5х = -6;

                                                                                           -----------------------------------------------------

                                                                                          -7х = -14 (все члены разделить на -7);

                                                                                            х = 2.

 

 

 

 х = 2;                             х = 2; 

у= 2 - 3 * 2;                   у = -4.